2003
DOI: 10.1021/ja037688a
|View full text |Cite
|
Sign up to set email alerts
|

Solventless Synthesis of Monodisperse Cu2S Nanorods, Nanodisks, and Nanoplatelets

Abstract: Cu2S nanocrystals with disklike morphologies were synthesized by the solventless thermolysis of a copper alkylthiolate molecular precursor. The nanodisks ranged from circular to hexagonal prisms from 3 to 150 nm in diameter and 3 to 12 nm in thickness depending on the growth conditions. High resolution transmission electron microscopy (HRTEM) revealed the high chalcocite (hexagonal) crystal structure oriented with the c-axis ([001] direction) orthogonal to the favored growth direction. This disk morphology is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
397
2
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(445 citation statements)
references
References 34 publications
35
397
2
5
Order By: Relevance
“…The crystallite facets are far more pronounced in the "large" 14 nm NCs than in the "smaller" ones. This is in accordance to previous reports of smaller nano-crystals that have a less defined crystal structure and faceting [25]. The devices were prepared by depositing the suspension of NCs in chloroform, employing a slow evaporation controlled method, onto Si/SiO 2 substrates with pre-patterned source-drain electrodes (Cr/Au, 2 μm spacing).…”
supporting
confidence: 70%
“…The crystallite facets are far more pronounced in the "large" 14 nm NCs than in the "smaller" ones. This is in accordance to previous reports of smaller nano-crystals that have a less defined crystal structure and faceting [25]. The devices were prepared by depositing the suspension of NCs in chloroform, employing a slow evaporation controlled method, onto Si/SiO 2 substrates with pre-patterned source-drain electrodes (Cr/Au, 2 μm spacing).…”
supporting
confidence: 70%
“…The solution phase synthesis of copper sulfide NCs have been based upon a sulfur oleylamine system 5,6) or a thermolysis of single-source precursor such as copper thiolat 7,8) and Cu(S 2 CNEt 2 ) 2 . 9) Recently, Korgel et al reported the composition control of copper sulfide NCs by changing the Cu/S source ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also provide context for several reported observations of high chalcocite phases in nanoparticles existing at low temperatures. 11,13 The uniquely low-temperature solid-solid transition observed for copper(I) sulfide suggests real-world applicability of this phase-change material, while making a broader call for characterization of additional materials whose phase diagrams enable transitions between functional crystal phases at room temperature.…”
mentioning
confidence: 99%